Quantification of recombinant immunotoxin delivery to solid tumors allows for direct comparison of in vivo and in vitro results - Mason-Osann, Emily (Sci Rep, 2015)
Solid tumors present challenges for delivery of protein therapeutics; current methods cannot quantify the functional effects of these agents. RG7787 (anti-mesothelin recombinant immunotoxin) is highly cytotoxic to pancreatic cancer cell lines, but with limited activity in vivo. To investigate this discrepancy, we developed a flow cytometry method to quantify the amount of RG7787 internalized per cell in tumors and used it to analyze tumor responses by determining the number of molecules of RG7787 internalized per cell in vivo and comparing it to that needed to kill cells in vitro. At a maximum tolerated dose of 7.5 mg/kg, tumor cells in vivo internalized a wide range of RG7787 with the average amount equivalent to the amount that induced growth arrest in vitro. However, 20% of cells accumulated 20,300 ITs per cell, sufficient to kill cells in vitro. At 2.5 mg/kg the top 20% of cells internalized enough RG7787 to only induce growth arrest. These data are in agreement with tumor responses; 22% regression following a 7.5 mg/kg dose and growth stabilization following 2.5 mg/kg. Comparing amounts of RIT delivered in vivo and in vitro can explain tumor responses and should facilitate the development of more active immunotoxins and other antibody based agents.